Mechanistic insights into the role of microRNAs in cancer: influence of nutrient crosstalk - Shah, Manasvi S.; Davidson, Laurie A.; Chapkin, Robert S. (Frontiers in Genetics, 2012)
A plethora of studies have described the disruption of key cellular regulatory mechanisms involving non-coding RNAs, specifically microRNAs from the let-7 family, the miR-17 family, miR-21, miR-143 and the miR-200 family, which contribute to aberrant signaling and tumor formation. Certain environmental factors, such as bioactive dietary agents, e.g., folate, curcumin, polyunsaturated fatty acids, are also thought to impact the progression and severity of cancer. In terms of the chemoprotective mechanisms of action, these bioactive dietary agents appear to act, in part, by modulating tissue levels of miR-16, miR-17 family, miR-26b, miR-106b and miR-200 family microRNAs and their target genes. However, the mechanisms of nutrient action are not yet fully understood. Therefore, additional characterization of the putative underlying mechanisms is needed to further our understanding of the biology, early diagnosis, prevention and the treatment of cancer. For the purpose of elucidating the epigenetic landscape of cancer, this review will summarize the key findings from recent studies detailing the effect of bioactive dietary agents on microRNA regulation in cancer.